Doing Poorly: The Real Income of American Children in a Comparative Perspective - Lee Rainwater; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1995)
This paper investigates the real living standards and poverty status of United States children in the 1990's compared to the children in 17 other nations, including Europe, Scandinavia, Canada and Australia. We find that American low-income children have lower real spendable income than do comparable children in almost every other nation studied. In contrast, high income United States children are far better off than are their counterparts in other nations. We also find persistently high child poverty rates in the United States compared with other nations. Demographic factors and the effectiveness of tax and transfer policies in reducing child poverty are also explored. The paper concludes with a discussion of results and their policy implications.
Keywords: 330; Kinder; Jugendliche; Lebensstandard; Armut; USA; Industrieländer